New high-speed system for controlling the parameters of a nuclear reactor in a nuclear power plant - Davydov, Roman; Antonov, Valery; Makeev, Sergey; Batov, Yury; Dudkin, Valentin; Myazin, Nikita (E3S web of conferences, 2019)
The necessity of modernizing current control systems for functional units of a nuclear power plant, as well as the development of new control systems with a high degree of reliability and speed, is substantiated. The advantages of using optical sensors and fiber-optic communication lines to solve these problems are noted. Cases for which it is necessary to develop new fiber-optic sensors for monitoring parameters, for example, the flow of coolant or feed water, are considered. In some of them, it is more expedient to use standard designs of fiber-optic sensors to control the operating parameters of various blocks, for example, to control the electric field strength. A device and a control scheme for the parameters of the units and systems of a nuclear power plant using fiber-optic communication lines have been developed. The results of measuring various parameters of a nuclear reactor are presented. They showed that our proposed fiber-optic control and monitoring system for nuclear power plants operates more reliably and efficiently than systems with analogue control and measurement channels. The use of fiber-optic systems allows real-time remote control and high-speed control in terms of issuing commands to devices. This is very important when servicing a nuclear power plant while it is operating in extreme conditions.